Assistance in Trademark Registration for Micro, Small and Medium Enterprises " Sri Lestari Fried Duck" - Ariyanti Ariyanti; Fadilla Dwi Lailawati; Listanto Tri Utomo; Lucky Dwi Ariani (Jurnal Aplikasi Dan Inovasi Ipteks "SOLIDITAS", 2023)
ABSTRACTBrand is one of the most important parts of a product. A brand can be an added value for a product, whether it is a product in the form of goods or services. This added value is very beneficial for business actors. Therefore, business actors try to continue to introduce their brands from time to time, especially consumers who are their target market. Sri Lestari fried duck business actors are actually aware that in establishing a business it is mandatory to have a name, but they do not understand the importance of registering their business name/trademark. The problem faced in Sri Lestari's fried duck business is the lack of understanding of the importance of registering a trademark for the sustainability of a more advanced business. And the process for registering the Bebek Goreng Sri Lestari trademark needs assistance so that the continuity of the registration process can still be monitored. The methods offered as an alternative solution to this problem are (1) Socialization of what a brand is and the importance of registering a trademark to increase business and be able to compete with other similar business actors, (2) Provide assistance in the trademark registration process. The results of this mentoring activity are the publication of supporting documents for trademark registration, namely NIB (Business Registration Number), Certificate of Development of Micro, Small and Medium Enterprises from the Department of Cooperatives, Industry and Trade of Malang City and Certificate of Trademark Registration. ABSTRACTBrand is one of the most important parts of a product. A brand can be an added value for a product, whether it is a product in the form of goods or services. This added value is very beneficial for business actors. Therefore, business actors try to continue to introduce their brands from time to time, especially consumers who are their target market. Sri Lestari fried duck business actors are actually aware that in establishing a business it is mandatory to have a name, but they do not understand the importance of registering their business name/trademark. The problem faced in Sri Lestari's fried duck business is the lack of understanding of the importance of registering a trademark for the sustainability of a more advanced business. And the process for registering the Bebek Goreng Sri Lestari trademark needs assistance so that the continuity of the registration process can still be monitored. The methods offered as an alternative solution to this problem are (1) Socialization of what a brand is and the importance of registering a trademark to increase business and be able to compete with other similar business actors, (2) Provide assistance in the trademark registration process. The results of this mentoring activity are the publication of supporting documents for trademark registration, namely NIB (Business Registration Number), Certificate of Development of Micro, Small and Medium Enterprises from the Department of Cooperatives, Industry and Trade of Malang City and Certificate of Trademark Registration.Keywords: Accompaniment, Business Identification Number, Trademark registration